2021
DOI: 10.1016/j.jenvp.2020.101541
|View full text |Cite
|
Sign up to set email alerts
|

Referent group specificity: Optimizing normative feedback to increase residential recycling

Abstract: Research has shown that messages containing descriptive normative feedback can induce behavior change in the direction of the norm. However, the literature is mixed regarding the relative influence of more specific referent groups. This study compared the effectiveness of social normative feedback at increasing waste diversion, across four referent groups varying in their degree of specificity. A sample of 1,560 single-family households in California was randomly assigned to one of six possible conditions: spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 58 publications
(70 reference statements)
2
17
0
3
Order By: Relevance
“…The analysis revealed that in line with previous studies, the same spatial-physical setting encouraged pro-environmental behavior, that is, water-saving behavior (Goldstein et al, 2008;Fornara et al, 2011;Schultz et al, 2019;Mertens and Schultz, 2021), but it was limited to low consumers, not all users. The differences in geographic proximity did not affect water use behavior, and this result is consistent with the findings of Mertens and Schultz (2021)'s waste recycling study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The analysis revealed that in line with previous studies, the same spatial-physical setting encouraged pro-environmental behavior, that is, water-saving behavior (Goldstein et al, 2008;Fornara et al, 2011;Schultz et al, 2019;Mertens and Schultz, 2021), but it was limited to low consumers, not all users. The differences in geographic proximity did not affect water use behavior, and this result is consistent with the findings of Mertens and Schultz (2021)'s waste recycling study.…”
Section: Discussionsupporting
confidence: 84%
“…A study on tax payment patterns indicated that social comparison had a greater effect when it was related to the behavior of a geographically closer community than that of a more distant one (Hallsworth et al, 2017). Contrastingly, studies on household recycling reported different results; that is, the effect of a city-level comparison was lower than that of a country-level comparison (Czajkowskia et al, 2019), and there was no difference between specific normative feedback about immediate neighbors (i.e., five closest neighbors) and generic normative feedback about other residents in their neighborhood (i.e., other similar households) (Mertens and Schultz, 2021). Another study on energy conservation programs using a normative feedback approach in the home energy reports indicated that increasing the level of proximity of the comparison from neighborhood to street level in-creased electricity savings; however, further increasing the comparison level to next-door neighbor leads to a drop in energy saving (Shen et al, 2016).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…information provision is considered to be a widely used tool for encouraging pro-environmental behavior and particularly waste sorting among households [7][8][9]. Social norms and rules can affect the consciousness, behavior and effect of waste sorting, and disobedience to social norms can lead to penalties or social sanctions [10,11]. The most prominent financial tool to promote waste sorting is monetary incentives which can be presented as rewards and penalties affecting an individual's behavior [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…More specifically, the findings indicate that, in smaller organisations, workers tend to perceive others as acting more often in environmentally friendly ways. This pattern could be related to norm specificity's effect (Mertens and Schultz, 2021). That is, proximal groups in terms of spatial proximity or shared attributes may be more important than distal, more generic groups to individuals assessing a given norm (Goldstein et al, 2008).…”
Section: Limitations and Future Researchmentioning
confidence: 99%